1991
DOI: 10.1002/cjce.5450690512
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size distribution on the performance of fluidized bed reactors

Abstract: This paper reviews recent results obtained in our laboratory and elsewhere which show the importance of particle size distribution (PSD) in fluidized beds. Fines content in itself, often used as a descriptor, is not a sufficient parameter to characterize the PSD effect. Broadening the PSD affects gas flow through the dense phase, produces smaller bubbles, leads to more particles in the dilute phase and causes earlier transition to the turbulent hydrodynamic regime of fluidization. Chemical conversion is theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(80 citation statements)
references
References 16 publications
7
69
0
Order By: Relevance
“…Experimental results have been presented on the impact of continuous-size distributions on the fluid mechanical behavior of bubbling beds, with effects ranging from minimum fluidization velocity, [10][11][12] bubble sizes, 13 pressure fluctuations, 14 presence of particles in bubbles, 10,15 etc. The contribution by Grace and Sun 14 represents one of the earliest reviews on the influence of particle-size distribution (PSD) on the quality of fluidization, and they summarized that a wider PSD (of Geldart Group A particles) culminates in enhanced reactor efficiency through improved interphase mass transfer and better gas-solid contacting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results have been presented on the impact of continuous-size distributions on the fluid mechanical behavior of bubbling beds, with effects ranging from minimum fluidization velocity, [10][11][12] bubble sizes, 13 pressure fluctuations, 14 presence of particles in bubbles, 10,15 etc. The contribution by Grace and Sun 14 represents one of the earliest reviews on the influence of particle-size distribution (PSD) on the quality of fluidization, and they summarized that a wider PSD (of Geldart Group A particles) culminates in enhanced reactor efficiency through improved interphase mass transfer and better gas-solid contacting.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution by Grace and Sun 14 represents one of the earliest reviews on the influence of particle-size distribution (PSD) on the quality of fluidization, and they summarized that a wider PSD (of Geldart Group A particles) culminates in enhanced reactor efficiency through improved interphase mass transfer and better gas-solid contacting. One factor impacting gas-solid interaction is the degree of species segregation, and a few efforts have reported on species segregation for continuous size distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, some studies have shown that a wide size distribution usually give the highest reactor efficiency, while the narrow blend give the lowest (Sun and Grace 1990), possibly associated with bubbling patterns in bed (Zenz and Othmer 1960, page 278). DEM simulations (Tagami, Mujumdar et al 2009) have also shown that systems with a wide PSD exhibit higher particle velocities around bubbles, while FINAL TECHNICAL REPORT 139 experiments (Grace and Sun 1991;Beetstra, Nijenhuis et al 2009) corroborated the enhancement of mixing through the production of smaller and faster-moving bubbles. However, it can be argued that if the lognormal distribution with σ/d sm = 70% exhibits the least extent of segregation due to its greatest width, why is it that the Gaussian distribution with the greatest width of σ/d sm = 30% did not similarly exhibit a well-mixed system?…”
Section: Axial Concentration Profilesmentioning
confidence: 85%
“…However, it can be argued that if the lognormal distribution with σ/d sm = 70% exhibits the least extent of segregation due to its greatest width, why is it that the Gaussian distribution with the greatest width of σ/d sm = 30% did not similarly exhibit a well-mixed system? Grace and Sun (Grace and Sun 1991) reviewed the influence of PSD on fluidized bed reactors and asserted that fines content per se is not a sufficient parameter to characterize segregation: their nature and the overall size distribution have to be considered. Correspondingly, future work is needed to get a clearer physical picture of the mechanisms leading to the non-monotonic segregation patterns observed here.…”
Section: Axial Concentration Profilesmentioning
confidence: 99%
“…For example, a wide size distribution has been observed to lead to smoother fluidization and better gas-solid contacting [12], whereas a narrow distribution may enhance bed stability (e.g., reduce segregation) [13]. In addition, the presence of fines (particles of 45μm diameter or less) may improve the performance of fluidized-bed mediums [14,15]; however, excessive fines may cause the powder to be too cohesive for proper fluidization [16].…”
Section: -Theoretical Relationsmentioning
confidence: 99%